2013
DOI: 10.1111/apha.12135
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phosphorylated heat‐shock protein 27 in response to acute ureteral obstruction in rats

Abstract: These data demonstrate that, in response to acute UUO, different forms of cellular stresses modulate HSP27 expression and phosphorylation in RMICs. This may affect the ability of renal cells to mount an effective cytoprotective response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…We have previously shown that phosphorylated HSP27 was increased in response to 6-and 12-h UUO (5). Our data also demonstrated the induction of phosphorylated HSP27 and HSP32 after 24-h UUO.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have previously shown that phosphorylated HSP27 was increased in response to 6-and 12-h UUO (5). Our data also demonstrated the induction of phosphorylated HSP27 and HSP32 after 24-h UUO.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have demonstrated that quercetin reduces the expression of HSPs (12). We (5) have previously shown induction of the phosphorylated form of HSP27 after 6-and 12-h UUO, and another study (1) has shown that HSP27 is required for induction of COX-2. Therefore, the effects of quercetin on HSP27, phosphorylated HSP27, HSP32, and HSP70 expression in the IM in response to 24-h UUO were examined.…”
Section: Quercetin Attenuated Cox-2 Induction In the Renal Im In Respmentioning
confidence: 57%
See 1 more Smart Citation
“…Salinthone et al [2007] demonstrated that Hsp27 inhibited this proliferation by affecting the rate of proliferation, not by halting the cell cycle progres- sion once the cell enters the cycle . So, Hsp27 is thought to have cytoprotective effects, promote reorganization of actin filaments and stabilize fibers when cells are exposed to oxidative stress [Huot et al, 1996;Carlsen et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The acute increases in intrarenal pressure are suggested to impact the tubular epithelial cells by mechanical stretch due to tubular distention. Changes in specific antioxidant enzymes and stress proteins in in vivo models of obstruction can be retrieved from the in vitro model of cells subjected to mechanical stress (8,40). Furthermore, it was recently shown that the inflammatory protein cyclooxygenase 2 increases in in vivo models of UUO and BUO (11,34) and in an in vitro cell model where renal medullary interstitial cells were subjected to 60-mmHg pressure for 6 h (7).…”
Section: Discussionmentioning
confidence: 99%